2022
DOI: 10.1101/2022.05.10.22274868
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autism spectrum disorders and brain volume link through a set of mTOR-related genes

Abstract: BackgroundLarger than average head and brain sizes are often observed in individuals with Autism Spectrum Disorders (ASDs). ASDs and brain volume are both highly heritable, with multiple genetic variants contributing. However, it is unclear whether ASDs and brain volume share any genetic mechanisms. Genes from the mammalian target of rapamycin (mTOR) pathway influence brain volume, and variants are found in rare genetic syndromes that include autism spectrum disorder features. Here we investigated whether vari… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Furthermore, according to ENIGMA consortium findings, genetic variants of PI3K‐AKT pathway genes are correlated with increased intracranial volume. Moreover, Arenella et al not only showed an association between variants in mTOR‐related genes, brain volume and ASD but also described a potential role for the genes involved in mTOR signalling (specifically genes included in both the sub‐pathways PI3K‐AKT–mTOR and RAS‐MAPK–mTOR) as mediators in the relationship between having a large brain and having ASD [57].…”
Section: Autism Spectrum Disordermentioning
confidence: 99%
“…Furthermore, according to ENIGMA consortium findings, genetic variants of PI3K‐AKT pathway genes are correlated with increased intracranial volume. Moreover, Arenella et al not only showed an association between variants in mTOR‐related genes, brain volume and ASD but also described a potential role for the genes involved in mTOR signalling (specifically genes included in both the sub‐pathways PI3K‐AKT–mTOR and RAS‐MAPK–mTOR) as mediators in the relationship between having a large brain and having ASD [57].…”
Section: Autism Spectrum Disordermentioning
confidence: 99%
“…In this issue, we see research on ASD being carried out in Arenella et al. 's study (Arenella, Mota, Teunissen, Brunner, & Bralten, 2023). The authors test whether variants in mTOR‐related genes are associated with ASD and if these genetic variants in some part help to explain the previously reported link between large brain volume and ASD.…”
mentioning
confidence: 99%
“…One of the challenges that Arenella et al. (2023) comment on is the heterogeneity in ASD. As Arenella et al.…”
mentioning
confidence: 99%
See 2 more Smart Citations